DSRC Technology in Vehicle-to-Vehicle (V2V) and Vehicle-to-Infrastructure (V2I) IoT System for Intelligent Transportation System (ITS): A Review - Aidil Redza, Khan; Mohd Faizal, Jamlos; Nurmadiha Osman, Osman; Muhammad Izhar, Ishak; Fatimah, Dzaharudin; You Kok, Yeow; Khairil Anuar, Khairi (Springer Nature, 2021)
Intelligent Transportation System (ITS) consisting of Vehicle Ad-hoc Networks (VANET) offers a major role in ensuring a safer environment in cities. For drivers and pedestrians. VANET has been classified into two main parts which are Vehicle to Infrastructure (V2I) along with Vehicle to Vehicle (V2V) Communication System. This technology is still in development and has not been fully implemented worldwide. Currently, Dedicated Short Range Communication (DSRC) is a commonly used module for this system. This paper focuses on both V2V and V2I latest findings done by previous researcher and describes the operation of DSRC along with its architecture including SAE J2735, Basic Safety Message (BSM) and different type of Wireless Access in Vehicular Environment (WAVE) which is being labeled as IEEE 802.11p. Interestingly, (i) DSRC technology has been significantly evolved from electronic toll collector application to other V2V and V2I applications such as Emergency Electronics Brake Lights (EEBL), Forward Collision Warning (FCW), Intersection Moving Assist (IMA), Left Turn Assist (LTA) and Do Not Pass Warning (DNPW) (ii) DSRC operates at different standards and frequencies subject to the country regulations (e.g. ITS-G5A for Europe (5.875–5.905 GHz), US (5.850–5.925 GHz), Japan (755.5–764.5 MHz) and most other countries (5.855–5.925 GHz)) where the frequencies affected most on the radius of coverage.